Isolation and identification of a novel Bacillus velezensis strain JIN4 and its potential for biocontrol of kiwifruit bacterial canker caused by Pseudomonas syringae pv. actinidiae - Zhao, Xin; Zhai, Yang; Wei, Lin; Xia, Fei; Yang, Yuanru; Yi, Yongjian; Wang, Hongying; Qiu, Caisheng; Wang, Feng; Zeng, Liangbin (Frontiers in Plant Science, 2024)
Bacterial canker is a devastating disease in kiwifruit production, primarily caused by Pseudomonas syringae pv. actinidiae. In this study, a strain of Bacillus velezensis named JIN4, isolated from a kiwifruit branch, showed antagonistic activity. The B. velezensis JIN4 strain was identified based on its morphological, physiological and biochemical characteristics, 16S rDNA, and gyrA sequences. Furthermore, the complete genome of the strain was elucidated, revealing the presence of three genes that confer resistance to antibiotics, including tetracycline, lincomycin, and streptomycin. Additionally, a cluster of nine secondary metabolite synthesis genes was identified. In the laboratory, the JIN4 strain exhibited nitrogen (N) and phosphorus (P) production, demonstrating plant growth-promoting and broad-spectrum inhibitory activities against pathogenic fungi and bacteria. In the field, the JIN4 strain demonstrated effective colonization of kiwifruit, increased antioxidant enzyme activity, induced resistance in kiwifruit plants, and achieved a control efficiency of 60.22% against kiwifruit bacterial canker. These results indicate that B. velezensis JIN4 is a potential biocontrol agent against kiwifruit bacterial canker.